A companion to environmental philosophy - Jamieson, Dale (Blackwell companions to philosophy., 2001)
"A Companion to Environmental Philosophy is a work in the field of environmental philosophy. This groun volume contains 36 original articles exemplifying the diversity of scholarship in this field."--BOOK JACKET.